High antimicrobial resistance in Salmonella spp. and Escherichia coli isolates from swine fecal samples submitted to a veterinary diagnostic laboratory in Colombia - Mantilla, Juan F.; Villar, David; Gómez-Beltrán, David A.; Vidal, Juana L.; Chaparro-Gutiérrez, Jenny J. (Revista Colombiana de Ciencias Pecuarias, 2021)
Background: Commensal microflora such as Escherichia coli and Enterococcus spp. are representative indicators of antimicrobial resistance (AMR) as they are part of the normal intestinal microflora and can acquire and disseminate AMR to pathogenic or zoonotic bacteria like Salmonella spp. Objective: To investigate the state of AMR among E. coli and Salmonella spp., potential pathogens in humans, isolated from cecal contents of pigs submitted to a veterinary diagnostic laboratory in Colombia from 2016 to 2019. Methods: Susceptibility testing was conducted using the Kirby-Bauer disk diffusion method according to the Clinical and Laboratory Standards Institute guidelines for antimicrobial zone diameter breakpoints. An E. coli strain (ATCC 25922) was used as the quality control organism. Isolates showing resistance to three or more antimicrobial classes were classified as multidrug-resistant (MDR) as defined by a joint group of the European Centre for Disease prevention and Control and the Center for Disease Control and Prevention of the USA. Results: A total of 112 E. coli and 192 Salmonella spp. colonies were isolated from 557 samples received between 2016 and 2019. In order of decreasing frequency, E. coli was resistant to tetracycline (100%), sulfamethoxazol-trimethoprim (97.5%), amoxicillin (86.4%), enrofloxacin (82.6%), tylosin (82.1%), doxycycline (59%), neomycin (50%), ciprofloxacin (45.5%), ceftiofur (35%), gentamicin (30%), tilmicosin (29%), and fosfomycin (12.5%). When compared with E. coli, Salmonella spp. was generally resistant to the same agents with slightly less resistance (between 10-30%) to eight of the antimicrobials tested. Salmonella spp. showed <20% resistance to three antimicrobials, as follows: neomycin (17%), gentamicin (16%), and fosfomycin (14%). Multi-resistance occurred in 68.7% (77/112) of E. coli and 70.3% (135/192) of Salmonella spp. isolates. Resistance of Salmonella spp. was alarming to all the critically important antimicrobials tested: fluoroquinolones (enrofloxacin, ciprofloxacin), ceftiofur (thirdgeneration cephalosporin), and macrolides (tylosin). Conclusions: According to our results, there is a high level of multidrug resistance (MDR) in E. coli and Salmonella spp. It is necessary to implement a nationwide antimicrobial resistance monitoring program in Colombia, together with proper antimicrobial prescribing guidelines for pigs. The indiscriminate use of antimicrobial growth promoters by the swine industry is generating widespread bacterial resistance and should be discontinued.